2016
DOI: 10.1038/srep32272
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Analysis and Histology on the Exact Same Tissue: Comprehensive Metabolomic Profiling and Metabolic Classification of Prostate Cancer

Abstract: We report a method of metabolomic profiling of intact tissue based on molecular preservation by extraction and fixation (mPREF) and high-performance chemical isotope labeling (CIL) liquid chromatography mass spectrometry (LC-MS). mPREF extracts metabolites by aqueous methanol from tissue biopsies without altering tissue architecture and thus conventional histology can be performed on the same tissue. In a proof-of-principle study, we applied dansylation LC-MS to profile the amine/phenol submetabolome of prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Altogether, 136 metabolites including different lipid species were identified (summary see Additional file 1: Table S1). We observed, as others [24], variation in the total amount of metabolites in the extracted tissues most likely related to sample size and composition of tissues. Therefore, we used relative intensities of metabolites in all data sets.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Altogether, 136 metabolites including different lipid species were identified (summary see Additional file 1: Table S1). We observed, as others [24], variation in the total amount of metabolites in the extracted tissues most likely related to sample size and composition of tissues. Therefore, we used relative intensities of metabolites in all data sets.…”
Section: Resultssupporting
confidence: 83%
“…Like in those two studies we observed an increase in levels of uracil in PC. Another interesting approach of metabolomic profiling of intact tissue was presented by Huan et al [24]; an approach based on molecular preservation by extraction and fixation and high-performance chemical isotope labeling LC-MS. They proposed a subset of five metabolites, including, adenosine monophosphate, uracil and spermidine, significant in comparison between PC and normal samples.…”
Section: Metabolism In Pcmentioning
confidence: 99%
“…A relatively stringent validation approach using three independent sample sets was employed by Huan and colleagues, although sample sizes were small [42]. For biomarker discovery, they used a set of 12 non-cancerous tissue samples and 13 PCa tissue samples (10 samples with >30% cancer proportion) obtained ex vivo by core biopsy from 16 subjects after prostatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Some metabolites were independently reported by different groups. In regard to PCa diagnosis, uracil [28,42,45,47] and proline [28,44,46,47] were most frequently reported as tissue biomarkers and uracil was independently validated in one study. In addition, there was some evidence for glycine, kynurenine, glycerol-3-phosphate, leucine, choline and citrate as potential diagnostic markers of PCa.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the measurement of small-molecule metabolites is of great importance due to the promise of linking the metabolite profiles to disease states. 6 Till now, the identification and quantification of metabolites are being mainly driven by the development of nuclear magnetic resonance [7][8][9] (NMR) and mass spectrometry 10 (MS) methodologies. These powerful tools are promising and will continue to generate metabolite profiles that can benefit biomarker discovery and medical diagnostic.…”
mentioning
confidence: 99%